Investment Climate And Ease of Doing Business In Indonesia After The Issuance of The Job Creation Law (Juridical Analysis On The Implementing Regulations On The Use Of Space) - Kurnia Lestari, Sukma; Ahmad, Suparji (Dinasti Research, 2024)
The Job Creation Law (Job Creation Law) and Government Regulation No. 21 of 2021 on the Implementation of Spatial Planning have a significant impact on Indonesia's investment climate and business environment. The Job Creation Law aims to create more jobs, protect business founders, boost investment, simplify business operations, and enhance worker protection and welfare by streamlining regulations that hinder economic growth. The implementation of Government Regulation No. 21 of 2021, which derives from the Job Creation Law, includes reducing bureaucratic hurdles, attracting more investment, and improving infrastructure management to foster a favorable and sustainable business environment. These measures are expected to enhance Indonesia's appeal as an investment destination for both domestic and international investors, thereby promoting sustainable economic growth. This growth aligns with sustainable development principles, emphasizing the conservation of natural resources and environmental sustainability for the benefit of current and future generations. The CK Law and Government Regulation No. 21/2021 mandate the simplification (streaming) of the spatial planning hierarchy, where in PP 21/2021 it is implemented in the Elimination of Provisions for the Determination of Strategic Areas, the integration of the technical content of marine space into one spatial plan product, the period for the preparation and determination of the RTRW is limited to a maximum of 18 months, starting from the implementation of the preparation of the RTRW, and the strategic environmental assessment is integrated into the technical material of the RTRW, are no longer compiled in separate documents. Another aspect of PP 21/2021 is that specifically for the Provincial RTRW, the technical material for the integrated coastal waters cargo must have received technical approval from the Minister of KKP.